BEHAVIOR OF FLAT REINFORCED-CONCRETE COLUMN SIZE (15x30) CM TO AXIAL CYCLIC LOADING : COMPARATION STUDY COLUMN WITH REINFORCEMENT AND STEEL PROFILE - Totok Andi Prasetyo; Agus Hadi Santosa W (Jurnal Syntax Transformation, 2023)
This research discusses the behavior of flat columns with the comparison of reinforced-concrete columns and IWF steel reinforcement. The research object took 4 column samples with a column size of 15x30 cm by comparing the reinforced-concrete column and concrete columns with IWF steel reinforcement. This study conducted comparisons with experimental tests, column capacity theory calculations, and calculations with the ANSYS19.2 program. The purpose of this study was to obtain the maximum axial load result, shorten the column, the relationship between stress and strain of the column, failure pattern of the column, and the ability of the column to withstand the number of floors in the sample of the reinforced-concrete column and concrete columns with IWF steel reinforcement. The results of the average maximum axial load of the test object for each sample column in the experimental test for K1 is 119,6 tons, K2 is 146,18 tons, K3 is 146,6 tons, and K4 is 167,46 tons, the maximum axial load in the column capacity calculation for column sample K1 is 130 tons, K2 is 159 tons, K3 is 157 tons, and K4 is 180 tons, and the maximum axial load in the ANSYS 19.2 program for column sample K1 is 122,7 tons, K2 is 138,86 tons, K3 is 150,14 tons, and K4 is 159,62 tons. The failure pattern occurred in column sample K1 is in the column span area, for sample K2 in the column span and pedestal area, the K3 column in the pedestal area, and the K4 column in the pedestal area. K1 column sample withstand 2-floors, K2 and K3 columns withstand 3-floors, and K4 column withstand 4-floors.